2024
DOI: 10.1101/2024.02.03.578493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoligomers targeting NF-κB and NLRP3 reduce neuroinflammation and improve cognitive function with aging and tauopathy

Devin Wahl,
Sydney J. Risen,
Shelby C. Osburn
et al.

Abstract: Neuroinflammation contributes to impaired cognitive function in brain aging and neurodegenerative disorders like Alzheimer’s disease, which is characterized by the aggregation of pathological tau. One major driver of both age- and tau-associated neuroinflammation is the NF-κB and NLRP3 signaling axis. However, current treatments targeting NF-κB or NLRP3 may have adverse/systemic effects, and most have not been clinically translatable. Here, we tested the efficacy of a novel, nucleic acid therapeutic (Nanoligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 112 publications
(213 reference statements)
0
6
0
Order By: Relevance
“…We observed similar results in terms of cognitive improvements and neuroinflammation reductions in the rTg4510 AD mouse model with NI112 4-week treatments. 64 Further neuropathological assessment using immunohistochemistry also showed a clear effect of NI112 treatment in the rTg4510 AD mouse model ( Fig. 2J, S3 ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…We observed similar results in terms of cognitive improvements and neuroinflammation reductions in the rTg4510 AD mouse model with NI112 4-week treatments. 64 Further neuropathological assessment using immunohistochemistry also showed a clear effect of NI112 treatment in the rTg4510 AD mouse model ( Fig. 2J, S3 ).…”
Section: Resultsmentioning
confidence: 80%
“…40,[53][54][55] Inflammasome inhibition has been intensely investigated as a novel target, as well as a common cure for a range of neurodegenerative and autoimmune diseases, 56,57 and using NF-κB and NLRP3 mRNA targeting and translation-inhibiting Nanoligomer combination (NI112) is a safe, effective, and targeted approach. [58][59][60][61][62][63][64][65] However, even other inflammasome-targeting smallmolecule therapeutics (e.g., MCC950) are limited by: 1) potential off-target effects; [66][67][68] and 2) the fact that they target only NF-κB or NLRP3 alone. NI112, an RNA therapeutic that crosses the blood-brain barrier, addresses problems with pan immunosuppressive therapies (such as steroids), and the cocktail potently inhibits neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first started with a maximum tolerable dose (MTD) assessment of the NF-κB and NLRP3 inhibitor combination NI112 ( nfkb1 (Sequence: AGTGGTACCGTCTGCTA) and nlrp3 (Sequence: CTTCTACTGCTCACAGG)). Prior studies have shown assessment of NI112 in relevant disease models (MS, AD, Prion/Creutzfeldt-Jacob Disease, neuroinflammation, and autoimmune diseases), 17,18,22,23,25,26 and Nanoligomer selectivity and high-binding affinity (K D 3.17 nM, 19,20 other PNA/RNA and PNA/DNA binding studies showed K D 5-8 nM 27 ) along with rapid biodistribution and clearance. We observed strong safety-toxicity profile in both animal models for longer-term repeat dosing (IP, 150 mg/kg, 3x a week for 12 weeks, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoligomer™ therapeutic platform generates safe, targeted, 34 and highly-specific (K D 3.37 nM 35,36 ) RNA-targeting molecules for facile delivery to targeted organs and both up-and downregulation of desired protein through translational and transcriptional regulation. [37][38][39][40][41][42] Nanoligomers utilize peptide nucleic acids (PNAs) as the sequence-specific binding component that demonstrate strong hybridization and specificity to their RNA (or DNA) sequence targets, 43 and exhibit no known enzymatic cleavage, leading to increased stability in human blood serum and mammalian cellular extracts. 44 Given the low K D , 35,36,43 high binding specificity, minimal off-targeting, 35,36 lack of any immunogenic response or accumulation in first pass organs, 34 absence of any observable histological damage to organs even for long (>15-20 weeks) treatments, [34][35][36]40 and facile delivery to the brain to counter neuroinflammation, 34,[37][38][39][40][41][42] we have demonstrated that Nanoligomers are a safe and targeted approach to screen for therapeutic targets in organoids and rodents for multiple neurodegenerative diseases aboard the International Space Station (ISS).…”
mentioning
confidence: 99%